2021
DOI: 10.15252/embr.202152764
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor depends on ligand‐binding domain dimerization for transcriptional activation

Abstract: Whereas dimerization of the DNA‐binding domain of the androgen receptor (AR) plays an evident role in recognizing bipartite response elements, the contribution of the dimerization of the ligand‐binding domain (LBD) to the correct functioning of the AR remains unclear. Here, we describe a mouse model with disrupted dimerization of the AR LBD (ARLmon/Y). The disruptive effect of the mutation is demonstrated by the feminized phenotype, absence of male accessory sex glands, and strongly affected spermatogenesis, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 63 publications
3
16
0
Order By: Relevance
“…The downregulation of Rhox5 expression ( Fig 7 ), which confirms our previous findings [8], further suggests that AR signaling may also be impaired in Sertoli cells. Recently, in a mouse model with disrupted dimerization of the AR ligand-binding-domain, a decreased expression of Hsd17b3 and of AR-regulated genes, such as Rhox5 and Insl3 , a higher percentage of Sertoli cells and a decreased production of round and elongated spermatids were found [46], which further supports our hypothesis that AR signaling may be defective in organotypic cultures. In the SPARKI (SPecificity-affecting AR KnockIn)-AR mouse model, which has a defect in binding to AR-specific DNA motifs while displaying normal interaction with the classical androgen response elements (AREs), it has been shown that Rhox5 expression is regulated by an AR-selective ARE, while Eppin expression is regulated by a classical, nonselective ARE [47].…”
Section: Discussionsupporting
confidence: 85%
“…The downregulation of Rhox5 expression ( Fig 7 ), which confirms our previous findings [8], further suggests that AR signaling may also be impaired in Sertoli cells. Recently, in a mouse model with disrupted dimerization of the AR ligand-binding-domain, a decreased expression of Hsd17b3 and of AR-regulated genes, such as Rhox5 and Insl3 , a higher percentage of Sertoli cells and a decreased production of round and elongated spermatids were found [46], which further supports our hypothesis that AR signaling may be defective in organotypic cultures. In the SPARKI (SPecificity-affecting AR KnockIn)-AR mouse model, which has a defect in binding to AR-specific DNA motifs while displaying normal interaction with the classical androgen response elements (AREs), it has been shown that Rhox5 expression is regulated by an AR-selective ARE, while Eppin expression is regulated by a classical, nonselective ARE [47].…”
Section: Discussionsupporting
confidence: 85%
“…Similar to other steroid receptors, it contains three domains: the amino-terminal domain (NTD), the DNA binding domain (DBD) and the ligand binding domain (LBD) [2]. Each domain has specific functions but communication as well as dimerization between different domains are required for full receptor activity [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the AR defects caused by the V770A mutation could only be explained in the case of the GR‐like LBD dimer, further confirming the presence of a transitional or intermediate state between the AR LBD homodimer and the GR‐like LBD homodimer. Of note, the W751R mutation that demonstrated a disruptive effect on AR activity in mice (El Kharraz et al, 2021), destabilizes AR LBD dimerization in both models reflective of its central location in H5 of the LBD dimerization interface, which is the lynch pin in the middle of two transitional states.…”
Section: Discussionmentioning
confidence: 98%